Multiculturalism and Interculturalism - Managing Diversity in Cross-Cultural Environment 2023
DOI: 10.5772/intechopen.109403
|View full text |Cite
|
Sign up to set email alerts
|

Perspective Chapter: Social Aspects of Violence – Cultural Dowry Practices and Intimate Partner Violence (IPV) in Pakistan

Abstract: Dowry is a transfer of materialistic goods or money from bride’s parents to bridegroom family at the time of marriage. However, as dowry demand rises, it has a significant detrimental impact on the lives of women. This chapter discusses the history of dowry and its practices, the positive and negative impact, and policy implications. The keywords used for this search were: “Dowry AND Pakistan,” “Pakistan culture AND Violence against women,” “social aspects AND Dowry practices,” and “Intimate-partner violence A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…These findings are in line with those from a study conducted in Delhi, India, which reported a 21% prevalence of IPV among pregnant women [35]. The lower rates of reported IPV in Pakistan and its neighboring country, India, can be attributed to the cultural norms prevalent in these regions, which share similar attitudes that prevent women from reporting IPV [36,37,38]. This cultural influence could lead to data underreporting due to social stigma, fear of retribution, and a lack of support systems.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are in line with those from a study conducted in Delhi, India, which reported a 21% prevalence of IPV among pregnant women [35]. The lower rates of reported IPV in Pakistan and its neighboring country, India, can be attributed to the cultural norms prevalent in these regions, which share similar attitudes that prevent women from reporting IPV [36,37,38]. This cultural influence could lead to data underreporting due to social stigma, fear of retribution, and a lack of support systems.…”
Section: Discussionsupporting
confidence: 89%
“…Although it fetches contentment as well as complications in one's life. But before entering into this contract there are some prerequisites, that include dowry in our Asian culture (Bhamani & Merchant, 2022). Dowry is, actually, a ritual in the event of marriage.…”
Section: Introductionmentioning
confidence: 99%